Interleukin-1β mediates endotoxin- and tumor necrosis factor α-induced RGS16 protein expression in cultured cardiac myocytes - Patten-Hamel, Monica; Stübe, Sabine; Thoma, Bryan Robert; Wieland, Thomas (Naunyn-Schmiedeberg's archives of pharmacology, 2003)
Endotoxin (LPS)-induced cardiac failure is associated with an up-regulation of RGS16 protein expression and repression of phospholipase C activity in vivo. Since the release of pro-inflammatory cytokines plays an important role in mediating LPS-induced myocardial dysfunction, we examined the effect of recombinant cytokines on the expression of RGS16 protein in neonatal cardiac myocytes. Myocytes in culture were treated with 50 ng/ml recombinant tumor necrosis factor alpha (TNFalpha), 2 ng/ml interleukin 1beta (IL-1beta), interleukin 6 (IL-6), interferon gamma (IFNgamma) or diluent (NaCl) for 24 h. Before stimulation with LPS (4 micro g/ml for 24 h) cells were treated with 200 ng/ml interleukin 1-receptor antagonist (IL-1ra), 500 ng/ml soluble TNF receptor (sTNFr), or NaCl for 1 h. Isolated membrane proteins were used for Western blot analysis. Cell-associated and secreted IL-1beta and TNFalpha protein content were determined in myocyte protein homogenates and cell culture supernatants by ELISA immunoblotting 3, 6, 24, 48 and 72 h after treatment with LPS. IL-1beta (1.75-fold) and TNFalpha (1.62-fold) but not IL-6 and IFNgamma induced RGS16 protein expression. LPS stimulated intracellular IL-1beta expression within 6 h (847.1+/-172.9 pg/3x10(6) cells) followed by an increase in extracellular secretion up to 70.8+/-8.1 pg/3x10(6) cells after 48 h. In contrast, intracellular protein concentrations of TNFalpha were almost not detectable (0.03+/-0.01 pg/3x10(6) cells), but extracellular secretion was induced by LPS with a maximum at 6 h (653.9+/-36.3 pg/3x10(6) cells). The LPS-induced increase in RGS16 (1.6-fold) was blunted by IL-1ra but not by TNFalpha scavenging. Interestingly, both, the IL-1beta- and TNFalpha-effect could be blocked by IL-1ra, indicating that also the TNFalpha-induced RGS16 expression is mediated by IL-1. We therefore conclude that LPS induces RGS16 protein expression by activation of the cytokine IL-1beta in cardiac myocytes. Our data substantiate the role of IL-1beta as an important mediator in LPS-induced cardiac failure.